Privacy in AI and the IoT: The privacy concerns of smart speaker users and the Personal Information Protection Law in China. (August 2022) - Liu, Yu-li; Huang, Luyan; Yan, Wenjia; Wang, Xinghan; Zhang, Ruochen
Abstract: In recent years, the development of Artificial Intelligence (AI) and the Internet of things (IoT) has attracted a lot of attention. One IoT device is the smart speaker that is equipped with an integrated assistant controlled by spoken commands. In the global smart speaker market, Chinese brands account for a significant share. Since smart speakers have a natural advantage when collecting user data in diverse scenarios, privacy and personal information protection have become crucial issues for both smart speaker manufacturers and users in China. This paper applies the socio-technical system (STS) framework to portray the technology subsystem, the industry/market subsystem and the regulators, law/regulation subsystem that are related to smart speakers in China, and how they interact with each other. It also uses focus group discussions to understand the smart speaker users' privacy concerns and the smart speaker industry's implementation of personal information protection. By employing the document analysis method, this study analyzes the laws and regulations related to privacy and personal information protection in the context of AI and the IoT. In particular, the potential impacts of the Personal Information Protection Law (PIPL) on smart speakers are discussed in detail. With its goal of balancing personal information protection and technological development, this paper provides recommendations for the regulatory bodies and the smart speaker industry players in China that can shed light on other countries and regions. Highlights: China's smart speaker market is still expanding and is monopolized by three major brands. The Cybersecurity Law (CSL), Data Security Law (DSL) and Personal Information Protection Law (PIPL) have laid a legal foundation for cyber security, data governance and personal information protection in China. Smart speaker users in China are mainly concerned about potential disruptions to their private lives and space, unequal privacy policies, opaque and excessive information collection and processing, as well as data security and integrity. The PIPL specifies the rights of individuals and the obligations of information processors. It may temporarily burden the smart speaker players, but it can help foster the sound development of the smart speaker industry in the long run.